2021
DOI: 10.1186/s13287-021-02419-1
|View full text |Cite
|
Sign up to set email alerts
|

High-efficiency c-Myc-mediated induction of functional hepatoblasts from the human umbilical cord mesenchymal stem cells

Abstract: Background Direct reprogramming of human fibroblasts to hepatocyte-like cells was proposed to generate large-scale functional hepatocytes demanded by liver tissue engineering. However, the difficulty in obtaining large quantities of human fibroblasts greatly restricted the extensive implementation of this approach. Meanwhile, human umbilical cord mesenchymal stem cells (HUMSCs) are the preferred cell source for HLCs with the advantages of limited ethical concerns, easy accessibility, and propag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In other studies, they found specific enzymatic digestion of amniotic membrane in which human amniotic epithelial stem cells (hAESCs) and amniotic mesenchymal stem cells (hAMSCs) were digested by protease enzymes trypsin and collagenases respectively 15,19,23,28 . Human amniotic epithelial stem cells are in a single layer bound with weak cellular interaction so trypsin dissociates them easily 20,27 .…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, they found specific enzymatic digestion of amniotic membrane in which human amniotic epithelial stem cells (hAESCs) and amniotic mesenchymal stem cells (hAMSCs) were digested by protease enzymes trypsin and collagenases respectively 15,19,23,28 . Human amniotic epithelial stem cells are in a single layer bound with weak cellular interaction so trypsin dissociates them easily 20,27 .…”
Section: Discussionmentioning
confidence: 99%
“…As a famous oncogene at 8q24.21 region, MYC was identified as one of the core genes regulating stem cell-like properties of cancer cells 68 . A recent study illustrated that high-efficiency c-Myc enhanced the conversion from mesenchymal stem cells to hepatoblast-like cells 69 . In this study, we found that MYC and its regulators ( HUWE1 and MYCBP2 ) were enriched in the signaling pathways regulating pluripotency of stem cells (Figure 4 A-B).…”
Section: Discussionmentioning
confidence: 99%
“…Studies should look for multi-year assessments of tumorigenicity in longer-living animals (e.g., pigs and sheep) and closer animal relatives to humans. Furthermore, there is an inherent tumour risk with using pluripotency factors, notably c-MYC (in OSKM), which has been shown as both dispensable and a facilitator of lineage-conversion [ 109 , 110 ]. As further research occurs, we may find efficient non-oncogenic factors for direct cellular reprogramming.…”
Section: Current Challenges and Future Perspectivesmentioning
confidence: 99%